Elaboración de una Guía Etnobotánica de los Árboles Frutales y Plantas Aromáticas Andinas del Cantón Sigchos - Lema Chuqui, Erika Jacqueline (2019)
This research was carried out is an ethnobotanical guide of the fruit trees and Andean aromatic plants in Sigchos. It was carried out with the purpose of identifying the existent vegetal species in the locality and to know the uses and cultural process that are related to the species mentioned above. For the data collection, a situational diagnosis was made of the study area, where two types of zones for the corresponding investigation were determined, this belongs to markets, later the select people were identified they were people who sell fruit and herbs aromatics, based on this the semi-structured interviews were applied to select people. Therefore, it was of vital importance to apply the interviews It was determined two locations (La Comunidad Cantera, Yaló) for the collection of botanical specimens. Through the on-site visit to the place, the collection of botanical samples and the taking of photographs of them was carried out. Also way, data was taken on various aspects of the plant, knowledge of the management of the species, the relationship of the uses and cultural processes that these species have. Afterwards, an inventory of the fruit trees and aromatic plants was carried out through the collection of information obtained in the field. The methodology used was qualitative and quantitative. Which 48 species were described according to their taxonomy, in the wild and cultivated, therefore, fifteen species of aromatic plants were determined, which seven of eight are aromatic and the others are used as condiments because they constitute a source of food, twenty species are fruit plants, and thirteen species have medicinal uses, these species are distributed in different areas, because they have adapted easily to the climatic factors that this canton has. These species have been determined in 21 families, which contain 48 species and six different gender, it is important to determine that the family Lamiaceae is the predominant of all, usually they are or perennial herbs, which are characterized by essential oil and aromatic; by means of the inventory of the INPC (botanically modified) records, 10 cultural processes were registered that are related to the use of the plants, these processes were identified in the localities where the study area was made. Finally, the information was systematized and reflected in the ethnobotanical guide. Concluding with the research it was determined that the species of fruit trees and aromatic plants are related to the ancestral knowledge therefore it is necessary to continue making new ethnobotanical studies in rural areas, establishing the use of plants with potential for tourism and local economy through cultural processes and ancestral knowledge.